Encouraging results of bowel and bladder management in spina bifida aperta in South India with quality of life scores in a tertiary care institution in South India - Jujju Jacob Kurian; Tarun John K. Jacob; John Mathai (Wolters Kluwer Medknow Publications, 2019)
Context: It is often a challenge to counsel parents with children operated for spina bifida aperta in developing countries. Data regarding the efficacy of simple measures and preventive are scarce. Aims: The aim of this study is to study such children for the incidence, prevalence of bowel bladder dysfunction, and the quality of life (QOL) in children who are involved with a multidisciplinary team in India. Materials and Methods: All children with spina bifida occulta were followed - QOL questionnaires (PIN Q, modified Barthels activities of daily living , and the visual analog score [VAS]) were used. Interventions, such as clean intermittent catheterization (CIC), bowel enemas, and surgical procedures, were studied. Results: A total of 68 children were assessed. Twenty-nine of these children over five were evaluated with QOL scores. The prevalence of incontinence of bowel and bladder was studied. The primary outcomes included the QOL scores, and the various surgical options help bowel and bladder management. Hydronephrosis in 17.95% of children <5 years and 65.5% of children over 5 years was noted. Nineteen children were socially independent for their bowel management. The Barthel index and PIN-Q showed a poor QOL in 27.6% and the VAS in 34.5% had the same. This translated to an acceptable QOL for over two-thirds of the children. Conclusions: Simple procedures and training for bowel management translate to a significant number of children being able to independently manage bowel care. About 30% of children develop hydronephrosis by 5 years; the decision to teach CIC must be made by then. We believe that positive counseling is given to the parents of children with spina bifida aperta as the children are capable of a reasonable QOL.